A Deterministic Propagation Model for Multipath Analysis at SKA Precursor Telescopes - A Case Study on MeerKAT - Phiri, T.; Davidson, David; Wiid, P. (IEEE, 2018)
IEEE Interferometers comprising large numbers of small diameter (LNSD) antennas are increasingly on the rise. This is in part driven by the technology and science around the Square Kilometre Array (SKA) and leads to progressively higher receiver sensitivities. Consequently, these new generation radio telescopes are more susceptible to radio frequency interference (RFI). The situation may be further aggravated when dishes are deployed in a compact fashion since this can result in a complex multipath environment. Focusing on the 64-dish SKA precursor, MeerKAT, multipath effects in the core area comprising 44 dishes of 13.5m diameter in a 1km radius are investigated. Due to complexity of the environment, empirical models offer limited benefit and hence numerical modelling becomes a compelling solution. We thus present a deterministic propagation model exploiting the method of moments (MoM) for antenna and real ground modelling and physical optics (PO) for representing scattering from metallic surfaces. In this way, the MeerKAT core was reproduced computationally and attenuation maps were produced revealing high and low risk regions.